Selective aqueous anion recognition in an anionic host - Noa Bar Ziv; Chengwei Chen; Bryce da Camara; Ryan R. Julian; Richard J. Hooley (iScience)
Summary: Water-soluble Fe4L44− cages can be synthesized in a multicomponent self-assembly process exploiting functionalized trigonal ligands, FeII salts, and water-soluble sulfonated formylpyridine components. The cages are soluble in purely aqueous solution and display an overall 4− charge, but are capable of binding suitably sized non-coordinating anions in the host cavity despite their anionic nature. Anions such as PF6− or AsF6− occupy the internal cavity, whereas anions that are too small (BF4−) or too large (NTf2−) are not encapsulated. The external anionic charge and sterically blocked ligand cores limit the exchange rate of bound anions, as no exchange is seen over a period of weeks with the anion-filled cages, and internalization of added PF6− by an empty cage takes multiple weeks, despite the strong affinity of the cavity for PF6− ions. In the future, this recognition mechanism could be used to control release of anions for environmental applications.